The effect of colloidal aggregates on fat crystal networks. Issue 1 (6th January 2017) - Chauhan, Raamanand R.; Dullens, Roel P. A.; Velikov, Krassimir P.; Aarts, Dirk G. A. L.
Abstract : An investigation into the role of fractal fumed silica aggregates in the crystallization and network formation of fat crystals. Abstract : We investigate the role of a colloidal model system in the crystallization and network formation of lipids. This system consists of fractal fumed silica aggregates. We look at the influence of different solid fat concentrations and fumed silica concentrations on the resulting gel network. Oscillatory rheology shows that the addition of silica to fat-in-oil gels does not significantly affect the magnitude of the storage modulus within the linear viscoelastic region. Interestingly, the range of this region is increased. Differential scanning calorimetry shows that the presence of silica leads to slightly earlier crystallization, though no significant effect on the melting profile of the formed network is found. Based on these observations, we propose that composite gel network structures have been formed. These results show that we have created reduced solid fat alternatives with similar rheological behaviour and thermal properties as the full-fat systems through the addition of colloidal silica.